Challenges of the social sector of the economy in Mexico: individualism, mistrust, and dependence - Blas-Yáñez, Sandra (Cooperativismo & Desarrollo, 2023)
Local rural production associations (LRPA) are entities recognized as part of the so-called social sector of the economy in Mexico. However, its monitoring, evaluation and strengthening is null, since, in terms of institutional and academic attention, cooperative societies dominate as the most studied figures of solidarity business organization. Therefore, the aim of this work is to determine the compatibility of the actions of a local association of pulque producers in central Mexico with the principles of the Social and Solidarity Economy (SSE). The study has a qualitative, descriptive, and exploratory approach. The results are the product of a situational diagnosis, prepared from participant observation, discussion groups, semi-structured interviews, and administrative file review. The findings show that the practices of the LRPA are far from cooperative principles, as an organizational culture of individualism, mistrust and paternalism persists, which negatively influence the capitalization of the association’s investments, training, and links. It is concluded that, to promote alternative economies, it is necessary to address the challenge of raising awareness about the principles and practices of the SSE, under a program of organizational cultural transformation that allows overcoming the paternalistic dependence that constrains associativity in Mexico.
Keywords: cooperative principles; social capital; alternative economy; diagnosis; LRPA